La transition agro-écologique des agricultures du Sud - Côte, François-Xavier; Poirier-Magona, Emmanuelle; Perret, Sylvain; Roudier, Philippe; Rapidel, Bruno; Thirion, Marie-Cécile (éditions Quae, 2019)
Food security, jobs, ecological transition of production and consumption modes and more One of the seventeen Sustainable Development Goals, agro-ecology could be one solution for meeting the forthcoming challenges for humanity. Cirad and AFD set out their thoughts on agro-ecology as a means for Southern agricultural systems to adapt to global change and on conditions for a successful agro-ecological transition.